Efektivitas Program Problem Based Learning Terhadap Tingkat Pengetahuan Mahasiswa Preklinik Selama Pandemi Covid-19 di FK-UMI - Oddang, Andi Zahra Shafanisa; Amir, Suliati P.; Musa, Inna Mutmainnah; Arfah, Arni Isnaini; Surdam, Zulfiyah (Yayasan Citra Cendekia Celebes, 2023)
The effectiveness of PBL discussions is one of the important factors that can ensure the success of learning in medical education with the KBK system. Effective PBL discussions can enhance the deep learning process for students. The effectiveness of PBL can also improve students' ability to solve problems. For medical students this will be very useful in preparing themselves as prospective doctors. This study aims to determine the effectiveness of PBL on the level of knowledge of preclinical students during the COVID-19 pandemic at the Faculty of Medicine, Muslim University of Indonesia. This study used an observational analytic method with a cross sectional design. This research was conducted in June – September 2021 at the Faculty of Medicine, Universitas Muslim Indonesia. The research subjects were 279 preclinical students. The sampling technique used is simple random sampling. Univariate analysis showed that overall preclinical students at the Faculty of Medicine, Muslim University of Indonesia were very interested, quite active, and had a good level of knowledge during online PBL with percentages of 82.19%, 66.94%, and 60.32%, respectively. Bivariate analysis showed that there was a relationship between the effectiveness of the online PBL method with students' motivation, interaction, and level of knowledge. The online method of PBL at the Faculty of Medicine, Muslim University of Indonesia is running quite effectively.